Incisional Hernia with Rare Finding of Liver as Content: A Case Report - Mogekar Smitha; Sudhir Jayakar (Journal of Clinical and Diagnostic Research, 2024)
Lumbar incisional hernia is an uncommon complication that affects the abdominal wall integrity, accounting for approximately 3.5% of all cases. It typically occurs following open nephrectomy or aortic aneurysm repair surgeries. Although rare, lumbar hernias can lead to discomfort, aesthetic issues, or even intestinal obstruction. In extremely rare cases, lumbar herniation of the liver can occur. Here, the authors present a case of a 60-year-old female patient with liver herniation through a lumbar incisional hernia and a history of pyelolithotomy for renal calculi. The authors performed an open hernia repair with meshplasty. Lumbar incisional hernias are rare and still difficult to manage. Computed tomography is the diagnostic method of choice in the evaluation of the parietal wall defect to choose the appropriate therapeutic management. Surgical management modalities are still poorly codified, with no precise recommendations, and this is probably due to the relative rarity of the cases.